The difference in soft tissue analysis before and after camouflage orthodontic treatment in Class II Division 1 skeletal malocclusion based on MC Namara analysis: comparative study - Miranti, Diandra Audyla; Mardiati, Endah; Evangelina, Ida Ayu; Laviana, Avi (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACT Introduction: The camouflage treatment of Class II division 1 malocclusion was performed on patients who are no longer able to be treated with functional orthodontic devices but it is still possible to be treated with orthodontic camouflage treatment. One of the possible methods to evaluate the results of orthodontic camouflage treatment of class II division 1 skeletal malocclusion was done by manual McNamara cephalometric analysis. The aim of the study was to determine the difference before and after orthodontic camouflage treatment of class II division 1 malocclusion using manual McNamara cephalometric analysis. Methods: This research is cross sectional comparative analytic. Determination of the sample was done by purposive sampling, which obtained 11 samples. McNamara's cephalometric analysis uses the Frankfort Horizontal Plane as a horizontal reference and determines a perpendicular line through the Nasion as a vertical reference. Statistical analysis was performed by t-test (p<0.05)t. Results: There were significant differences in the results of soft tissue analysis of the nasolabial angle, upper lip cant, and the distance of the maxillary incisors to the A-Pog point (p<0.05). There were no significant differences in analysis of point A to N perpendicular, condylion to point A , condylion to point of gnation, LAFH, mandibular plane angle, facial axis angle, pogonion distance to N perpendicular, and mandibular incisor distance to point A-Pog (p >0.05). Conclusions:Orthodontic camouflage treatment of skeletal class II division 1 malocclusion results in changes in the soft tissue of the nasolabial angle, upper lip cant, and the distance of the maxillary incisors to the A-Pog point. While point A to N perpendicular, condylion to point A, condylion to point of gnation, LAFH, mandibular plane angle, facial axis angle, pogonion distance to N perpendicular, and the distance of the mandibular incisor to the A-Pog point did not change.KEY WORDS: Skeletal malocclusion, Class II division 1, orthodontic camouflage treatment, mcnamara cephalometric analysis.Perbedaan analisis jaringan lunak sebelum dan setelah perawatan ortodonti kamuflase pada maloklusi skeletal kelas II divisi 1 berdasarkan analisis MC Namara: studi komparatifABSTRAK Pendahuluan: Perawatan ortodonti kamuflase maloklusi kelas II divisi 1 dilakukan pada pasien yang sudah tidak mungkin dirawat dengan alat ortodonti fungsional tetapi masih mungkin dilakukan dengan perawatan ortodonti kamuflase. Salah satu cara evaluasi hasil perawatan ortodonti kamuflase maloklusi skeletal kelas II divisi 1, dilakukan dengan analisis sefalometri McNamara secara manual. Tujuan penelitian menganalisis perbedaan hasil analisa sefalometri jaringan lunak metode McNamara sebelum dan setelah perawatan kamuflase maloklusi skeletal kelas II divisi I Metode: Jenis penelitian cross sectional analitik komparatif. Penentuan sampel dilakukan secara purposive sampling, diperoleh 11 sampel. Analisis sefalometri McNamara menggunakan Frankfort Horizontal Plane sebagai referensi horizontal dan menentukan garis tegak lurus melalui Nasion sebagai referensi vertikal. Analisis statistik dilakukan dengan uji pairedt-test (p<0,05). Hasil: Terdapat perbedaan signifikan hasil analisis jaringan lunak sudut nasolabial, cant bibir atas, dan hubungan insisif rahang atas terhadap titik A-Pog (p<0,05). Tidak terdapat perbedaan signifikan analisis titik A ke N perpendicular, condylion ke titik A, condylion ke titik gnation, LAFH, mandibular plane angle, facial axis angle, jarak pogonion ke N perpendicular, dan jarak gigi insisif rahang bawah ke titik A-Pog (p>0,05). Simpulan: Perawatan ortodonti kamuflase pada maloklusi skeletal kelas II divisi 1 menghasilkan perubahan jaringan lunak sudut nasolabial, cant bibir atas, dan jarak insisif terhadap titik A. Titik A ke N perpendicular, condylion ke titik A, condylion ke titik gnation, LAFH, mandibular plane angle, facial axis angle, jarak pogonion ke N perpendicular, sedangkan jarak gigi insisif rahang bawah ke titik A-Pog tidak mengalami perubahan.KATA KUNCI: Maloklusi skeletal, kelas II divisi 1, ortodonti kamuflase, analisis sefalometri jaringan lunak, McNamara.